Penguatan Pendidikan Akhlak pada Pendidikan Dasar/MI - Suparlan Suparlan (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2022)
ABSTRACT (ENGLISH) Education is a conscious and planned effort in the process of mentoring and learning for individuals so that they grow and develop into human beings who are independent, responsible, creative, knowledgeable, healthy and have noble character (UU No.20 of 2003). While the purpose of education in Law no. 20 of 2003 concerning the National Education System is: National Education functions to develop capabilities and shape dignified national character and civilization in order to educate the nation's life, aims to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible country”. Morals come from the Arabic plural 'from the mufradat form